Evaluation of Holistic and Balanced Education at Thursina International Islamic Boarding School Malang - Anwar, Khairil; In’am, Akhsanul; Khozin, Khozin; Farid, Farid (International Journal of Education, Culture, and Society, 2025)
The holistic and balanced education implemented by Thursina IIBS Malang develops all basic human potential maximally and in balance, including spiritual, emotional, social, emotional, aesthetic, intellectual and physical potential. The aim of the research is to describe the evaluation of holistic and balanced education at Thursina IIBS Malang. Qualitative research method with case study type. Data collection techniques using interviews, observation and documentation. data processing techniques with data reduction, data presentation and drawing conclusions. Data validity technique using source triangulation. The educational evaluation process in Thursina is not only focused on the academic aspect but the student's life experience as a whole. The research results show that the evaluation of holistic and balanced education at Thursina IIBS Malang does not only assess aspects cognitive but also includes affective and psychomotor aspects. The evaluation carried out by Thursina IIBS focused on transformation of consciousness, assessment of spiritual values ​​and development of all human potential maximally and in balance, including spiritual potential (spiritual, emotional, social, aesthetic), aqliyah (intellectual and creativity) and jasadiyah (physical). The implications of this research are as study material in developing educational evaluations in realizing graduate profiles with Islamic personalities, broad insight and leadership qualities.